Exploring whether relationship mobility and goal congruence in travel groups enhance tourists’ pro-environmental behaviors: new insights from social cognitive theory - Gao, Junxi; Deng, Weiwei (Frontiers in Psychology, 2025)
This study addresses the research gap in group-level pro-environmental behaviors by establishing a social cognitive theoretical model within travel groups. Employing a quantitative design and structural equation modeling, it examines key antecedents, the mediating role of relationship mobility, and the moderating effect of Goal Congruence. Findings reveal that environmental emotion/values, impression management, and relationship mobility significantly promote low-cost pro-environmental behaviors, while only environmental emotion/values positively affects high-cost behaviors. Relationship mobility mediates the effects of environmental emotion/values and impression management on low-cost behaviors, and the effect of impression management on high-cost behaviors. Goal Congruence moderates the effects of environmental emotion/values and impression management on both low-cost and high-cost behaviors (except environmental emotion/values’ direct effect on high-cost). While limited by its focus on travel groups and self-reported data, the research significantly advances understanding by shifting to the group level in tourism, empirically validating distinct pathways for different behavior costs, and highlighting relationship mobility and Goal Congruence’s critical roles. It offers practical strategies for leveraging group dynamics.